Sea ice analysis and forecasting : towards an increased resilience on automated prediction systems - Carrieres, Tom; Buehner, Mark; Toudal Pedersen, Leif (Cambridge University Press, 2017)
A comprehensive overview of the science involved in automated prediction of sea ice, for sea ice analysts, researchers, and professionals.